PENGARUH KUALITAS PELAYANAN, KUALITAS PRODUK DAN PROMOSI TERHADAP KEPUTUSAN PEMBELIAN PADA OPTIK TUNGGAL SEMPURNA CABANG LIPPO MALL KEMANG - Fitriani; Lucy Nancy Simatupang (Jurnal Manajemen, 2018)
This study aims to determine the effect of Service Quality, Product Quality and Promotion on the purchase decision. used in the research is quantitative methods and assessment of the results of this study based on the answers to the questionnaire given to respondents using Likert Scale. The population in this study is all customers at Optik Tunggal Sempurna and sample in this study is amounted to 58 respondents. Methods of analysis in this research using descriptive analysis, The Instrument (Validity and Reability), Classical Assumption Test (Normality, Multicoloniarity, Heteroskidasity, and Autocorrelation), Corelattion, Linier regression analysis, t test, F test and Determinant coefficient R2. The results of the t test (partially), has obtained results that variable Product Quantity is significant on the purchase decision of PT.Optik Tunggal Sempurna. While the variable Service Quality and Promotion have no effect and does not significantly influence the purchase decision of PT.Opiik Tunggal Sempurna. From test f (simultaneously), the result that the third variable and significant influence on the purchase decision of Optik Tunggal Sempurna